Proposing a Financial Reporting Transparency Model for the Development of Health Insurance from the Perspective of Experts in the Ministry of Health and Medical Education - Zourani, Elham; Sotudeh, Reza; Piri , Habib (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The objective of this study is to identify the factors influencing financial reporting transparency in the health insurance sector. Methodology: This research employed both qualitative and quantitative methods. In the qualitative section, the statistical population consisted of managers and experts in the healthcare field from the Zahedan University of Medical Sciences. Data collection was conducted through semi-structured interviews, and theoretical saturation was achieved after 11 interviews. The data were then analyzed using grounded theory coding. In the quantitative section, 384 questionnaires were distributed randomly among employees in the health insurance sector. The SmartPLS software was used to estimate and evaluate the relationships in the financial reporting transparency model for the health insurance sector. Findings: Based on the proposed model, 12 main codes were extracted, including: "implementation of accounting standards, establishment of accounting laws and regulations, need for financial reporting transparency, economic development in health insurance, evaluation of financial reporting quality, meritocracy in the hiring of managers, internal political and economic communications, control over financial and operational policies of the company, market pressure, and capital market competition." Conclusion: The model and concepts extracted from participants’ responses indicate that there are various reasons and motivations for adopting financial reporting transparency in the health insurance sector. Moreover, the designed model clearly demonstrates that the motivations and reasons for adopting this system are fulfilled as a result of its implementation.